2014
DOI: 10.1210/en.2013-1736
|View full text |Cite
|
Sign up to set email alerts
|

Programming of the Hypothalamic-Pituitary-Adrenal Axis by Neonatal Intermittent Hypoxia: Effects on Adult Male ACTH and Corticosterone Responses Are Stress Specific

Abstract: Intermittent hypoxia (IH) is an animal model of apnea-induced hypoxia, a common stressor in the premature neonate. Neonatal stressors may have long-term programming effects in the adult. We hypothesized that neonatal exposure to IH leads to significant changes in basal and stress-induced hypothalamic-pituitary-adrenal (HPA) axis function in the adult male rat. Rat pups were exposed to normoxia (control) or 6 approximately 30-second cycles of IH (5% or 10% inspired O₂) daily on postnatal days 2-6. At approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…We have observed a similar phenomenon with intermittent neonatal hypoxia with respect to the behavior of the HPA axis in adults (Chintamaneni et al. ). In that study, less severe intermittent hypoxia (10% O2) produced a different HPA axis “programming” response than more severe intermittent hypoxia (5% O2).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…We have observed a similar phenomenon with intermittent neonatal hypoxia with respect to the behavior of the HPA axis in adults (Chintamaneni et al. ). In that study, less severe intermittent hypoxia (10% O2) produced a different HPA axis “programming” response than more severe intermittent hypoxia (5% O2).…”
Section: Discussionsupporting
confidence: 73%
“…; Chintamaneni et al. , ). Therefore, discussion of the long‐term effects of late gestation fetal hypoxia is worthwhile in this context, particularly because studies of the long‐term effects of fetal hypoxia are more numerous and comprehensive than neonatal hypoxia in precocial species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, although chronic exposure to moderate hypoxia throughout development reduced basal cortisol levels in 120 hpf zebrafish larvae, it did not affect basal cortisol levels or the response to a net/handling stress protocol in adults [5]. In rats, while several studies have shown that hypoxia can programme the responsiveness of the HPA axis, whether the adult corticosterone stress response is reduced, enhanced or unaffected by fetal or perinatal hypoxia depends on when during development the hypoxic stressor is applied, its severity and duration [20,21]. To what extent HPI axis programming by hypoxia depends on similar exposure windows in zebrafish awaits further experimentation.…”
Section: Discussionmentioning
confidence: 97%